Gestão das passagens aéreas na Universidade Federal de Goiás: uma análise otimizada - Silva, Paulo Cezar Bispo da (2021)
This research explores the administrative process of purchasing airline tickets at the Federal University of Goiás – UFG, demonstrating the financial impact that is generated by the time interval between the request and the actual purchase of airline tickets. Using as a guiding guide the structured method DMAIC, proposed by Six Sigma, and mapping the process, it was possible to identify the causes of variability, measuring the processing time in each step and its impact on the total time of the process. With the identification of inefficiencies, it was possible to define intervention proposals. The results show that from the proposed optimization, the purchase interval is reduced, providing a reduction in the price of airline tickets, and thus bringing financial gains to the institution.